Biological inspiration to solve complexity in intelligent and adaptive manufacturing systems - Leitão, Paulo (2010)
The current demand for customization, flexibility and responsiveness constitutes a challenge to achieve intelligent and adaptive manufacturing systems. Understanding how in nature the complex things are performed in a simple and effective way, allows us to copy them and develop complex and powerful adaptive and evolvable systems. The paper overviews some principles found in nature and biology and analyses the application of bio-inspired solutions to solve complex engineering problems, especially in the manufacturing field. The paper also discusses the effective applicability of these methods in several areas of manufacturing systems and analyses the available agent-based tools to support the simulation of bio-inspired solutions.